Keabsahan Perkawinan Beda Agama di Kota Makassar: Studi Analisis Undang-Undang Perkawinan dan Hukum Islam - Iqrahayu; Maloko, M. Thahir (Shautuna: Jurnal Ilmiah Mahasiswa Perbandingan Mazhab, 2023)
Ulama agreed that women who are Muslim (Muslimah) are forbidden to marry between men who are not from the same religion as her. However, in reality interfaith marriages still continue to occur in society. The main problem in this study is how to analyze interfaith marriage in Makassar City, Biringkanaya District. The purpose of this study is to determine interfaith marriage in the city of Makassar, Biringkanaya District and to know and understand the relevance of the application of interfaith marriage with the concept of Law No. 1 of 1974 and know and understand the validity of interfaith marriage according to Islamic Law. Researchers use qualitative methods, this research is field research, which is a direct review of the location studied to obtain data, then the data is used as the main data or primary data. While the nature of this research is descriptive, that is, it describes regularly the problem under study in accordance with the data obtained then analyzed. The results of this study show that authentically interfaith marriage according to the concept of Law No. 1 of 1974 concerning marriage states that a valid marriage is a marriage carried out according to their respective religions and beliefs. Law No. 1 of 1974 does not expressly prohibit interfaith marriage, resulting in a legal vacuum. According to Islamic Law on interfaith marriage in Indonesia explains that the legal basis for interfaith marriage is not permissible because it involves differences in faith.